2013
DOI: 10.1152/ajprenal.00112.2013
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factors in the kidney and relationship to hypertension

Abstract: Members of the epidermal growth factor (EGF)-family bind to ErbB (EGFR)-family receptors that play an important role in the regulation of various fundamental cell processes in many organs including the kidney. In this field, most of the research efforts are focused on the role of EGF-ErbB axis in cancer biology. However, many studies indicate that abnormal ErbB-mediated signaling pathways are critical in the development of renal and cardiovascular pathologies. The kidney is a major site of the EGF-family ligan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 133 publications
(129 reference statements)
2
35
0
Order By: Relevance
“…[65][66][67] EGFRs are localized along the nephron, 65 and they play key roles in normal kidney physiology and pathogenesis. For example, EGF is important in renal cyst formation, 68 repair of AKI, 67 progression in CKD, 67,69 and development of kidney carcinoma. [70][71][72] At the cellular level, EGF is especially critical in renal sodium 69,73 and magnesium homeostasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[65][66][67] EGFRs are localized along the nephron, 65 and they play key roles in normal kidney physiology and pathogenesis. For example, EGF is important in renal cyst formation, 68 repair of AKI, 67 progression in CKD, 67,69 and development of kidney carcinoma. [70][71][72] At the cellular level, EGF is especially critical in renal sodium 69,73 and magnesium homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, EGF is important in renal cyst formation, 68 repair of AKI, 67 progression in CKD, 67,69 and development of kidney carcinoma. [70][71][72] At the cellular level, EGF is especially critical in renal sodium 69,73 and magnesium homeostasis. 74,75 Therefore, it is The phosphoserine band intensities were normalized by their respective total AQP2 loading controls (mean6SD; n=4).…”
Section: Discussionmentioning
confidence: 99%
“…Dominant negative EGFR overexpression mice exhibited less interstitial fibrosis than wild type mice after subtotal renal ablation or following angiotensin II infusion (18). It was also reported that EGF-EGFR axis regulates sodium transport and development of hypertension (19). In this point of view, decreased EGF may be beneficial by inhibiting the activation of EGFR.…”
Section: Ju Et Al In Sci Transl Medmentioning
confidence: 95%
“…Many investigators have studied the role of EGF and EGFR in the ENaC regulation [44,45], however the contradictory results have been reported [44,45]. Taruno et al [26] have report that an inhibitor of EGFR diminishes the ENaC-mediated Na + transport in renal A6 epithelial cells by activating EGFR via the change in the membrane tension caused by hypotonicity, suggesting that activation of EGFR would have a stimulatory action on the ENaC-mediated Na + transport in renal A6 epithelial cells.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%